Populism in Europe - an Overview - Segbers, Klaus; Hegedüs, Daniel; Kuzio, Taras; Glahn, Cosima (2018)
Abstract: Populism as such is not new in the dictionaries of political and cultural sciences. The history of humankind is relatively rich in people and movements trying to convince people that simple and simplifying answers on complex questions may work. But in the last five or so years, there is a resurgence of populism across continents, societies and traditional political cleavages. As Brexit, the current U.S. dministration and many other events demonstrate, populism is shaping and influencing the political processes in Europe and far beyond. Against this background, the Center for Global Politics (www.global-politics.org) of Freie Universität Berlin organized a roundtable event for the annual convention of the Association for Slavic, East European and Eurasian Studies (ASEEES) which took place last fall (2017) in Chicago. The topic of this event was "Populism in Eastern Europe". The idea was to analyze empirical examples of populism in Eastern Europe and beyond, to discuss with the atten